Sex disparity in dialysis and kidney transplantation over 20 years in Korea - Miyeun Han; Jong Cheol Jeong; Yun Yung Cho; Curie Ahn; Yeong Hoon Kim (The Korean Society of Nephrology, 2023)
Background Sex disparity is prevalent in organ transplantations worldwide. This study aimed to understand sex disparities in dialysis and kidney transplantation in Korea over the last 20 years. Methods Data for incident dialysis, waiting list registration, and donors and recipients were retrospectively collected between January 2000 and December 2020 from the Korean Society of Nephrology end-stage renal disease registry and the database of the Korean Network for Organ Sharing. Data regarding the proportion of females for dialysis, waiting list, and kidney transplantation donors or recipients were analyzed using linear regression analysis. Results The average proportion of females on dialysis over the past 20 years was 40.5%. The proportion of females on dialysis was 42.8% in 2000, and decreased to 38.2% in 2020, showing a decreasing trend. The average proportion of women on the waiting list was 38.4%, which was lower than that for dialysis. The average proportion of female recipients in living donor kidney transplantation and female living donors were 40.1% and 53.2%, respectively. The overall proportion of female donors in living donor kidney transplantation showed an increasing trend. However, there was no change in the proportion of female recipients in living donor kidney transplantation. Conclusion Sex disparities in organ transplantation exist, including an increasing trend of female donors in living donor kidney transplantation. Further studies are needed to identify the biological and socioeconomic factors involved to resolve these disparities.